Proof: Get Iterate End Expr 68
Let's prove the following theorem:
if the following are true:
- expression state at time 68 = "iterate_args"
- arguments stack at time 68 = [ [ ], [ ] ]
- parent stack at time 68 = [
joe.jump()
, [ ] ]
then the expression at time 69 = joe.jump()
Proof:
Given
1 | expression state at time 68 = "iterate_args" |
---|---|
2 | arguments stack at time 68 = [ [ ], [ ] ] |
3 | parent stack at time 68 = [ joe.jump() , [ ] ] |
# | Claim | Reason |
---|---|---|
1 | the expression at time (68 + 1) = joe.jump() |
if expression state at time 68 = "iterate_args" and arguments stack at time 68 = [ [ ], [ ] ] and parent stack at time 68 = [ joe.jump() , [ ] ], then the expression at time (68 + 1) = joe.jump() |
2 | 68 + 1 = 69 | 68 + 1 = 69 |
3 | the expression at time (68 + 1) = the expression at time 69 | if 68 + 1 = 69, then the expression at time (68 + 1) = the expression at time 69 |
4 | the expression at time 69 = joe.jump() |
if the expression at time (68 + 1) = the expression at time 69 and the expression at time (68 + 1) = joe.jump() , then the expression at time 69 = joe.jump() |
Comments
Please log in to add comments